A Scientometric Analysis of Green HRM Research (2000-2024) Using VOSviewer: Mapping the Intellectual Structure and Emerging Themes from Scopus Data - Judijanto, Loso; Mayasari, Nanny; Nampira, Ardi Azhar (Westscience Press, 2025)
This study presents a comprehensive scientometric analysis of Green Human Resource Management (Green HRM) research published between 2000 and 2024, utilizing Scopus-indexed data and VOSviewer for bibliometric visualization. Through keyword co-occurrence, co-authorship, and country collaboration analyses, the study maps the intellectual structure, identifies dominant research clusters, and highlights emerging themes in the field. The findings indicate that Green HRM has matured into a multidisciplinary domain anchored by themes such as sustainability, green behavior, human resource practices, and green innovation. Over time, the focus of research has shifted from macro-level issues—like environmental sustainability and policy integration—toward micro-level constructs, including employee engagement, green leadership, and organizational citizenship behavior for the environment. Influential author networks, particularly from China, Malaysia, and Europe, shape the development of the field, while cross-national collaboration continues to grow, especially within Asia and the Middle East. The study reveals knowledge gaps in linking behavioral outcomes to organizational performance and emphasizes the need for future research in digital HR transformation, performance metrics, and underrepresented geographic contexts. These insights provide a roadmap for scholars and practitioners aiming to deepen the strategic and operational integration of sustainability within human resource systems.